ITIL Framework 3: Analysis of Management Information Technology Services at XYZ Hospital in Semarang - Vivi Widya Larasati; Sri Murtini; Rani Raharjanti; Marliyati Marliyati (Cita Konsultindo Research Center, 2023)
This study aims to analyze the management of information technology services using the ITIL V3 Framework at XYZ Hospital Semarang. Data were obtained through interviews and questionnaires. Respondents in this study were employees in a section that explicitly manages SIMRS XYZ and SIMRS XYZ users at the managerial level. The results of this study indicate that the XYZ Semarang hospital has fulfilled operational service procedures following the ITIL Framework version 3. Measuring the maturity level of information technology service management at the XYZ Semarang hospital is categorized in maturity level 4 or managed, namely activities or business processes that have been well organized and corrective management processes have been implemented. Recommendations for improvement strategies are given to achieve the desired maturity level, namely by improving the management of existing information technology services and information systems. Keywords: framework ITIL V3, service operation, maturity level, and information technology